Strategi Komunikasi Pemasaran Instagram Online Shop (Studi Kasus Online Shop Mishalot Florist) - Jonathan Kuswandy; Sisca Aulia (Kiwari, 2022)
Marketing communication plays an important role in building the image of an organization. Marketing communication can generate and develop consumer awareness of a company's products / services so that consumers are aware of the products / services offered. This is the way that it aims to generate marketing, focusing on delivering the products and services that consumers need directly. This research is a qualitatively descriptive study. Descriptive qualitative research is research using case study methods. The results of this study show that the marketing communication strategy carried out by Mishalot Florist through Instagram social media proved not all of them meet the existing marketing mix, but, their consumers know the information about the product quite clearly. The selection of media used should better optimize and support marketing communication activities in other ways so that the application of marketing communication can run more to keep up with the development of a very modern era like now.   Komunikasi pemasaran memegang peranan penting dalam membangun citra  suatu organisasi. Komunikasi pemasaran dapat membangkitkan dan mengembangkan kesadaran konsumen terhadap produk/ jasa suatu perusahaan sehingga konsumen sadar akan produk/ jasa yang ditawarkan. Inilah cara yang bertujuan untuk menghasilkan pemasaran, berfokus pada penyampaian produk dan layanan yang dibutuhkan konsumen secara langsung. Penelitian kualitatif deskriptif adalah penelitian menggunakan metode studi kasus (case study).  Hasil dari penelitian ini menunjukan bahwa strategi komunikasi pemasaran yang dilakukan Mishalot Florist melalui media sosial Instagram terbukti tidak semuanya memenuhi bauran pemasaran yang ada akan tetapi, konsumen mereka mengetahui informasi seputar produk cukup jelas. Pemilihan media yang digunakan sebaiknya lebih mengoptimalkan dan mendukung kegiatan komunikasi pemasaran dengan cara lain sehingga penerapan komunikasi pemasaran dapat berjalan lebih bisa mengikuti perkembangan jaman yang sangat modern seperti sekarang.